2004
DOI: 10.1074/jbc.m304754200
|View full text |Cite
|
Sign up to set email alerts
|

Substitution in Position 3 of Cyclosporin A Abolishes the Cyclophilin-mediated Gain-of-function Mechanism but Not Immunosuppression

Abstract: Both immunosuppressive drugs cyclosporin A (CsA) 1 and tacrolimus (FK506) are believed to inhibit antigen-specific activation of lymphocytes by blocking T cell receptor (TCR) signaling cascades through targeting the Ca 2ϩ /calmodulindependent Ser/Thr phosphatase calcineurin (1, 2), which represents a specific bottleneck of antigen-receptor signaling. The drugs alone do not inhibit the enzymatic activity of calcineurin. CsA and FK506 bind to and inhibit calcineurin only after interaction with their respective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Comparison of the NCI3-mediated suppression of the NFAT-and NF-jB-luciferase reporter gene expression with the CsA-mediated effects indicated that the pathways inducing the activity of these two transcription factors exhibited different sensitivity to NCI3 and CsA. Whereas CsA inhibited the expression of both reporter gene constructs with similar efficiencies (IC 50 of 2.0 and 4.0 nM) [18], NCI3 exhibited IC 50 values of 2 AE 0.1 lM for the NFAT and 7 AE 1 lM for the NF-jB-driven construct. Interestingly, the TNF-amediated stimulation of the NF-jB reporter plasmid in Jurkat cells remained unaffected by CsA and NCI3 ( Table 2), suggesting that in this signaling pathway calcineurin is not involved.…”
Section: Nci3 Blocks Specifically Tcr Signalingmentioning
confidence: 98%
See 3 more Smart Citations
“…Comparison of the NCI3-mediated suppression of the NFAT-and NF-jB-luciferase reporter gene expression with the CsA-mediated effects indicated that the pathways inducing the activity of these two transcription factors exhibited different sensitivity to NCI3 and CsA. Whereas CsA inhibited the expression of both reporter gene constructs with similar efficiencies (IC 50 of 2.0 and 4.0 nM) [18], NCI3 exhibited IC 50 values of 2 AE 0.1 lM for the NFAT and 7 AE 1 lM for the NF-jB-driven construct. Interestingly, the TNF-amediated stimulation of the NF-jB reporter plasmid in Jurkat cells remained unaffected by CsA and NCI3 ( Table 2), suggesting that in this signaling pathway calcineurin is not involved.…”
Section: Nci3 Blocks Specifically Tcr Signalingmentioning
confidence: 98%
“…The biotinylated and non-biotinylated VIVIT peptide (MAGPHPVI-VITGPHEE) [18], the reversed VIVIT peptide (EEHPGTIVIVPH-PGAM), and the biotinylated RII peptide (DLDVPIPGRFDRRV-SVAAE-OH) were synthesized by solid-phase peptide synthesis (Quartett, Berlin, Germany).…”
Section: Preparation Of Calcineurin and Synthesis Of Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bcl-10 phosphorylation events can both positively and negatively regulate NF-kB activation (reviewed in [12]). Several studies have reported that not only NFAT, but also NF-kB activation by antigen-specific T-cell stimulation is dependent on the phosphatase activity of CaN, identified by using the immunosuppressive drug cyclosporine A (CsA) [13][14][15][16]. CsA binds to its matchmaker protein cyclophilin A and, subsequently, this complex inhibits the Ser/Thr phosphatase activity of CaN [17][18][19][20].…”
mentioning
confidence: 99%